Transportation Systems for Livable Communities - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2012)
TRB2019s Conference Proceedings on the Web 6: Transportation Systems for Livable Communities summarizes the results of an October 2010 conference that explored the challenges of incorporating livability into transportation programs and projects.The proceedings consist of presentation summaries from the opening sessions and panels, and summaries of key research needs and possible performance measures identified in the discussion groups.

Sustainable Critical Infrastructure Systems: A Framework for Meeting 21st Century Imperatives: Report of a Workshop - National Research Council (The National Academies Press, 2009)
For the people of the United States, the 20th century was one of unprecedented population growth, economic development, and improved quality of life. The critical infrastructure systems-water, wastewater, power, transportation, and telecommunications-built in the 20th century have become so much a part of modern life that they are taken for granted. By 2030, 60 million more Americans will expect these systems to deliver essential services. Large segments and components of the nation's critical infrastructure systems are now 50 to 100 years old, and their performance and condition are deteriorating. Improvements are clearly necessary. However, approaching infrastructure renewal by continuing to use the same processes, practices, technologies, and materials that were developed in the 20th century will likely yield the same results: increasing instances of service disruptions, higher operating and repair costs, and the possibility of catastrophic, cascading failures. If the nation is to meet some of the important challenges of the 21st century, a new paradigm for the renewal of critical infrastructure systems is needed. This book discusses the essential components of this new paradigm, and outlines a framework to ensure that ongoing activities, knowledge, and technologies can be aligned and leveraged to help meet multiple national objectives.

Pathways to Urban Sustainability: Challenges and Opportunities for the United States - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Cities have experienced an unprecedented rate of growth in the last decade. More than half the world's population lives in urban areas, with the U.S. percentage at 80 percent. Cities have captured more than 80 percent of the globe's economic activity and offered social mobility and economic prosperity to millions by clustering creative, innovative, and educated individuals and organizations. Clustering populations, however, can compound both positive and negative conditions, with many modern urban areas experiencing growing inequality, debility, and environmental degradation. The spread and continued growth of urban areas presents a number of concerns for a sustainable future, particularly if cities cannot adequately address the rise of poverty, hunger, resource consumption, and biodiversity loss in their borders. Intended as a comparative illustration of the types of urban sustainability pathways and subsequent lessons learned existing in urban areas, this study examines specific examples that cut across geographies and scales and that feature a range of urban sustainability challenges and opportunities for collaborative learning across metropolitan regions. It focuses on nine cities across the United States and Canada (Los Angeles, CA, New York City, NY, Philadelphia, PA, Pittsburgh, PA, Grand Rapids, MI, Flint, MI, Cedar Rapids, IA, Chattanooga, TN, and Vancouver, Canada), chosen to represent a variety of metropolitan regions, with consideration given to city size, proximity to coastal and other waterways, susceptibility to hazards, primary industry, and several other factors.

Transitioning Toward Sustainability: Advancing the Scientific Foundation: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine
In 1999 the National Academies of Sciences, Engineering, and Medicine released a landmark report, Our Common Journey: A Transition toward Sustainability, which attempted to \